ONE HAND PASS TRAINING MODEL IN BASKETBALL FOR 13-15 YEARS - Milia, Mike Okta; Sulaiman, Iman; Widiastuti; Subandi, Oman U. (Gladi : Jurnal Ilmu Keolahragaan, 2025)
ABSTRACT This research aims to improve basketball one-hand pass passing skills for 13-15 years old. The implementation of the research was carried out from May to June 2024 which took place at the Stamford Rafles Hils Cibubur basketball court The research was attended by all warriors academy basketball athletes aged 13-15 years, which consists of 30 athletes. The method used in this study is Research & Development with the ADDIE method. The instrument used is a basketball one-hand pass skill assessment instrument for 13-15 years old that has been validated by basketball experts and experts. Based on the data of the initial test of one hand pass skills, an average result of 140.7 Then after being given training materials in the study to improve basketball one hand pass skills for 13-15 years old for 8 meetings, a final test was carried out with an average result of 178.0 in this study there was an increase in basketball one hand pass skills for 13-15 years old.